American tragedy: the uncensored story of the Simpson defense - Schiller, Lawrence (Random House, 1996)
This account will finally explain for the first time, in the uncensored words of Simpson's closest confidants and attorneys, such mysteries as the missing Louis Vuitton bag and the Bronco chase - where was Simpson going and why? What is the real reason Simpson submitted to a lie detector test and what precisely happened when he got the results? Which members of Simpson's team believed his story, which ones had doubts? Why did the defense know from the beginning that they. Had at least a hung jury, and why was Simpson told he was going home even before the verdict came down? Why was Simpson's reputation more important to him than whether he was convicted? How did Simpson's team stage an elaborate deception during the jury's visit to his Rockingham mansion? What did a leading forensic psychiatrist discover about O.J. during his face-to-face examination? Why was Johnnie Cochran afraid to return to Simpson's holding cell during final Arguments? You've heard the speculations and rumors; now read what really happened. But American Tragedy goes far beyond such revelations, for in these pages the reader will discover who Simpson really is and why he is able to insist upon his innocence even to this day.